AI-mediated ecological resilience & Gender-Based Violence (GBV) in climate-vulnerable communities - Jibril, Abubakar Muhammad (Privietlab, 2025)
Climate change is not just an environmental risk but also a multiplier of gender-based violence (GBV), especially among impoverished communities that have been displaced and lack access to effective legal remedies. The research explores how environmental stresses such as floods, drought, and forced migration of communities amplify GBV in Sub-Saharan African and Southeast Asian climate-exposed areas. It also deals with the use of artificial intelligence (AI) for enhancing legal systems, risk pattern detection, and building gender-sensitive climate resilience. Using a qualitative socio-legal methodology, the study combines doctrinal legal analysis, feminist legal theory, and artificial intelligence tools like natural language processing (NLP) in analyzing public discourse, identifying policy gaps, and evaluating regulatory gaps. The key findings report increases in domestic violence, sexual exploitation, child marriage, and trafficking during the climate disasters, especially during the recovery phases. Although AI has promise in monitoring GBV trends online and in revealing policy blind spots on climate, ethical concerns are raised, especially around accessibility, surveillance concerns, and cultural exclusion. The study demands integrating GBV safeguards into climate adaptation legislation, codesign of moral AI systems with at-risk consumers, and binding international law to prevent GBV in the aftermath of disasters. It offers a rights model that connects gender justice, legal reform, and ethical application of AI.